2018
DOI: 10.1590/2179-8087.025216
|View full text |Cite
|
Sign up to set email alerts
|

Growth Stress in Peltophorum dubium and its Correlation with the Growth Variables

Abstract: The exploitation of valuable native timber species in forest restoration projects has emerged as a promising strategy to make restoration financially viable. There are few studies regarding the quality of timber from restoration plantations. The aim of this study was to analyze growth stresses by determining the longitudinal residual strain (LRS) and evaluate their correlation with the growth variables in the species Peltophorum dubium (Spreng.) Taub in a 14-year old restoration plantation. Eighteen individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…The success of P. dubium (high survival rate) may be related to the high phenotypic plasticity, related to high irradiance and low incidence of pests and disease in this species [32][33][34]. In addition, P. dubium is a pioneer species that presents a pronounced growth of the root system and, consequently, develops a larger leaf area and a balanced aerial part [35].…”
Section: Discussionmentioning
confidence: 99%
“…The success of P. dubium (high survival rate) may be related to the high phenotypic plasticity, related to high irradiance and low incidence of pests and disease in this species [32][33][34]. In addition, P. dubium is a pioneer species that presents a pronounced growth of the root system and, consequently, develops a larger leaf area and a balanced aerial part [35].…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al (2017) confirmed the good phytosanitary status of Cedrela fissilis Vell. trees, and Xavier et al (2018) found that the wood of Peltophorum dubium (Spreng.) Taub.…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…Peltophorum dubium (Sprengel) Taubert é uma espécie nativa popularmente conhecida como canafístula, pertencente à família Fabaceae (XAVIER et al, 2018). Possui tolerância a baixas temperaturas, adaptando-se ao clima subtropical e temperado, fator que favorece sua extensa ocorrência natural, desde o estado da Bahia ao Rio Grande do Sul, sendo encontrada principalmente nas florestas latifoliadas semidecíduas (RAMPIM et al, 2014).…”
Section: Introductionunclassified